Basic water measurement instruments enhance irrigation management in Nepal - Neupane, Nilhari; Nepal, Santosh; Bhatt, Dinesh; Lautze, Jonathan F. (CGIAR, 2024)
Basic water measurement instruments introduced by IWMI in collaboration with the Department of Water Resources and Irrigation enabled an irrigation project in Western Nepal to improve agricultural productivity